Dataset on fuel properties and volatile organic compounds from chemically synthesized biomass components for modeling and predicting biomass properties in pyrolysis processesDeposited in the Knowledge Base of UPWr - Ewa Syguła; Jacek Łyczko; Andrzej Białowiec (Data in Brief)
This data set provides a controlled and precise analysis of chemically synthesized biomass mixtures, focusing on the key structural components - lignin, cellulose, and hemicellulose - in specific ratios. The biochars were produced at 200°C to 600°C, yielding 204 biochar samples and 12 crude blends. Detailed data include parameters such as mass yield (MY), energy density ratio (EDr), and energy yield (Ey), as well as bulk density, moisture content, organic matter, elemental analysis (C, H, N, S, O), higher heating value (HHV) and ash-free heating value (HHVdaf). In addition, an analysis of volatile organic compounds (VOCs) released from biochar was also conducted, providing key insights into the emissions associated with biochar production. The dataset facilitates accurate modeling and predicting biomass properties under thermal conditions, supporting bioenergy and materials science research. The analyses were conducted in triplicate, generating 612 data points for each parameter. This dataset provides a valuable foundation for research involving lignocellulosic materials, enabling consistent characterization, reproducibility, and comparative analysis for future research.